1994
DOI: 10.1038/eye.1994.131
|View full text |Cite
|
Sign up to set email alerts
|

The role of light scatter in the degradation of visual performance before and after Nd:YAG capsulotomy

Abstract: The aim of this study was to determine whether capsulotomy size influences visual performance. Snellen visual acuity and forward light scatter (light scattered towards the patient's retina, but out of the focussed retinal image) measurements using simple computer graphics based on van den Berg's technique were used to measure visual performance. Twelve patients were studied: 4 had small central capsulotomies through undilated pupils and 8 had wide capsulotomies through dilated pupils. The two groups were match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
0
15
0
1
Order By: Relevance
“…Indeed, several studies showed that glare disability was worse with a small capsulotomy than with a large capsulotomy. 16,17 Holladay et al 23 assumed that Nd:YAG capsulotomy of equal or larger than the pupillary diameter under scotopic conditions is necessary for recovering image intensity and for lessening glare disability. We verified that both contrast VA and glare VA are recovered in eyes that undergo capsulotomy of larger than the pupillary size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several studies showed that glare disability was worse with a small capsulotomy than with a large capsulotomy. 16,17 Holladay et al 23 assumed that Nd:YAG capsulotomy of equal or larger than the pupillary diameter under scotopic conditions is necessary for recovering image intensity and for lessening glare disability. We verified that both contrast VA and glare VA are recovered in eyes that undergo capsulotomy of larger than the pupillary size.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, if the capsulotomy is too small, visual function may not be recovered. Indeed, previous studies showed that glare disability in eyes with a small capsulotomy is worse than those with a large capsulotomy despite no significant difference in VA. [16][17][18] However, to date, there is no study about the relationship between capsulotomy size and contrast sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a capsulotomy smaller than the pupil has been demonstrated to affect forward light scatter measurements [5] and automated perimetry results more than a capsulotomy wider than the pupil [3].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Buehl et al (2005), the correlations between VA and the central area of the posterior capsule versus a larger area differed. In a pilot study regarding forward light scatter after different sizes of capsulotomy, Goble et al (1994) found that a smaller capsulotomy influenced forward light scatter and probably resulted in more glare disability than a larger opening in the posterior capsule. This indicates that there would be more symptoms of PCO if the cell proliferation was more centrally located.…”
Section: Discussionmentioning
confidence: 99%